2008
DOI: 10.1002/art.24182
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps strength and the risk of cartilage loss and symptom progression in knee osteoarthritis

Abstract: Objective To determine the effect of quadriceps strength in individuals with knee osteoarthritis (OA) on loss of cartilage at the tibiofemoral and patellofemoral joints (assessed by magnetic resonance imaging [MRI]) and on knee pain and function. Methods We studied 265 subjects (154 men and 111 women, mean ± SD age 67 ± 9 years) who met the American College of Rheumatology criteria for symptomatic knee OA and who were participating in a prospective, 30-month natural history study of knee OA. Quadriceps stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
225
2
9

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 249 publications
(252 citation statements)
references
References 34 publications
13
225
2
9
Order By: Relevance
“…Some longitudinal studies have demonstrated a role of lower muscle strength in the onset (16,22,39) and progression (40,41) of radiographic knee OA, while one other longitudinal study showed that in malaligned or lax knees, progression of radiographic knee OA was associated with higher muscle strength (42). We showed an association between lower muscle strength and self-reported knee instability.…”
Section: Discussionmentioning
confidence: 46%
“…Some longitudinal studies have demonstrated a role of lower muscle strength in the onset (16,22,39) and progression (40,41) of radiographic knee OA, while one other longitudinal study showed that in malaligned or lax knees, progression of radiographic knee OA was associated with higher muscle strength (42). We showed an association between lower muscle strength and self-reported knee instability.…”
Section: Discussionmentioning
confidence: 46%
“…The finding of lower isometric muscle strength in symptomatic versus asymptomatic legs is supported by previous studies reporting a protective effect of muscle strength on knee pain (12,37). O'Reilly et al observed lower quadriceps strength in symptomatic versus asymptomatic legs, but did not match case and control knees for radiographic disease stage (38).…”
Section: Discussionmentioning
confidence: 83%
“…Muscle weakness is considered a potentially modifiable (9) risk factor of KOA and quadriceps muscle strengthening is recommended by the current Osteoarthritis Research Society International KOA treatment guidelines (10). Previous studies reported a reduction of knee pain (11)(12)(13) following quadriceps strengthening exercise but no significant modification of structural (i.e., radiographic) disease progression (11) with training intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Limited evidence exists to support muscle strength as a predictor of knee OA progression (13). Yet, over time, people with knee OA who have greater quadriceps strength report less pain and superior functional ability compared to their weaker counterparts (37). Quadriceps strength has been studied widely in relation to knee OA, however muscles around the hip stabilising the pelvis also have an effect on adduction forces around the knee that may result in increased compression of the medial compartment (38) and influence the pathogenesis and progression of OA.…”
Section: Muscle Strengthmentioning
confidence: 99%